Innovation-Based Research Using Structural Flexibility and Acceptance Model (SFAM) - Solimun; Adji Achmad Rinaldo Fernandes (Cogent Business & Management, 2023)
The research objectives are as follows: (1) Develop a solid structural model assuming normality and homoscedasticity. (2) Obtain the property estimator of the flexible and robust SFAM structural model. (3) Obtaining hypothesis testing of each relationship built from the flexible and strong SFAM structural model. This research is integrated with a flexible and robust modeling approach based on nonparametric smooth spline regression analysis (RNSS) that can capture the shape and robustness of relationships dependent on empirical data. There are at least three transformation methods namely SRS, MSI and RASCH that will be used in SFAM development. The results obtained are the development of a flexible structural model in the form of relationships between variables and a robust structural model from the two assumptions, then the estimator properties and hypothesis testing of each relationship are built from the two models. The authenticity of this research is very evident in the discovery of a new model, namely SFAM that can accommodate various things, which are the weaknesses of various existing analytical tools such as recursive and recursive models, more than one endogenous variable, flexible and strong models.
Keywords: 650; Flexible and Sturdy Structural Modeling; SEM; SFAM